Application of cold-formed steel built-up sections in building construction - Lau, Hieng Ho; Ting, Chui Huon; Tang, Fu Ee; Mei, C. (The Institute of Cold-formed Metal Structures, 2010)
Researchers have noticed the advantages of utilizing built-up sections in steel structures. Several studies have shown that the performance of a structure is improved using built-up sections. Current industry design has taken advantage of cold-formed steel sections with limited in-depth knowledge and comprehensive design codes on built-up sections. The potential of built-up sections is limited without strong research and development works. These sections are generally used in cold-formed steel construction to resist loads induced in a structural member when a single section is insufficient to carry the applied load. By doing so, the weight of the structure can be greatly reduced while maintaining a large clear span.Its popularity in construction projects has stimulated the growth of research studies in this area. This paper aims to present the applications of cold-formed steel built-up sections in the construction industry and to present the experimental study conducted on stub and intermediate built-up columns. Experimental study was done on 16 built-up back-to-back C-channels sections and 8 built-up box sections in compression. The specimens were compressed between pinned end and fixed end conditions at various lengths ranging from 250mm to 1600mm. The column test strengths were compared with the theoretical design strengths, which were calculated using the Effective Width Method (EWM) and also the Direct Strength Method (DSM). The results show that compared to single C-channel columns, built-up columns possess greater lateral stiffness thus doubling the load carrying capacity with no significant changes in axial displacement.